Akokoid Comparative Wordlist (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Akokoid, in this paper, refers to the nine speech forms which are spoken in Akoko North-West Local Government Area of Ondo State in South-Western Nigeria. These speech forms are Arigidi, Erushu, Afa, Oge, Aje, Udo, Oyin, Igashi and Uro. Since the 1970's, scholars have lumped these speech forms together as dialects of the same language without any detailed lexicostatistic investigation. Thus, the major objective of this paper is to determine whether the speech forms are really dialects of the same language through lexicostatistic analysis. Data were collected from 34 informants spread across the nine geographical areas where the speech forms are spoken through the direct interview method. In analyzing these data, Swadesh's principles of lexicostatistics were used. The lexicostatistic figures reveal that Arigidi and Erushu are 88.5% cognate, so they are classified as dialects of Arigidi. Afa, Oge, Aje, Udo, Oyin, Igashi and Uro are 81% cognate, so they are classified as dialects of the same language called Owon (meaning tongue). Two distinct but fairly related languages were identified within the nine speech forms. These are Arigidi and Owon, jointly referred to as Akokoid by virtue of their Akoko root. Therefore, there is no justification for lumping them together as dialects of a single language.